Genetic and morphological evidences for the existence of a new species of contracaecum (Nematoda: Anisakidae) parasite of phalacrocorax brasilianus (Gmelin) from Chile and its genetic relationships with congeners from fish-eating birds - Garbin, Lucas; Mattiucci, Simonetta; Paoletti, Michela; González-Acuña, Daniel; Nascetti, Giuseppe (Journal of Parasitology)
Contracaecum australe n. sp. is described from the Neotropic cormorant Phalacrocorax brasilianus in Chile based on morphology and the sequence analyses of multiple loci, i.e., mitochondrial cytochrome oxidase 2, mtDNA cox-2, the small subunit of the mitochondrial ribosomal RNA gene, rrnS, and the ITS-1 and ITS-2 regions of nuclear ribosomal DNA. Moreover, sequence analysis of the same genes was carried out on the morphospecies Contracaecum chubutensis Garbin et al. (2008) from Phalacrocorax atriceps. Further, genetic relationships are presented between C. australe n. sp. and C. chubutensis with respect to the related congeners from fish-eating birds previously characterized genetically on the same genetic markers, i.e., Contracaecum rudolphii A, B, C, D, and E, Contracaecum septentrionale, Contracaecum microcephalum, Contracaecum bioccai, Contracaecum pelagicum, Contracaecum micropapillatum, Contracaecum gibsoni, and Contracaecum overstreeti. Several phylogenetic analyses (MP, NJ, and BI) inferred from mitochondrial genes (cox-2, rrnS) were congruent in depicting C. australe n. sp. and C. chubutensis as forming distinct clades, highly supported, from the remainder of the Contracaecum taxa considered; thus, it validates their specific status. Further, analyses of the ITS-1 and ITS-2 sequence data of C. australe n. sp. and C. chubutensis supported their distinction with respect to the 2 sibling species, C. rudolphii D and C. rudolphii E, previously detected from Phalacrocoracidae of Australia. Morphological analysis and the differential diagnosis of male specimens of C. australe n. sp. enabled the detection of differences in a number of characters, including spicule length, peculiar shape of male tail, paracloacal papillae disposition, and shape and bifurcation depth of interlabia. According to the genetic and morphological results obtained, the erection of a new taxon from fish-eating birds of the Austral region is given and its formal description is presented. Phylogenetic trees support both C. australe n. sp. ...